2007
DOI: 10.2353/ajpath.2007.060696
|View full text |Cite
|
Sign up to set email alerts
|

The Microenvironment Controls CDX2 Homeobox Gene Expression in Colorectal Cancer Cells

Abstract: The homeobox gene CDX2 plays a major role in development, especially in the gut, and it also acts as a tumor suppressor in the adult colon. Using orthotopic and heterotopic xenografts of human primary colorectal tumor cells and cell lines in nude mice, we addressed the effect of the microenvironment on CDX2 expression. In cells expressing CDX2 at a high level in culture, this level was maintained in subcutaneous grafts but was reduced when implanted into the cecum wall. Reciprocally, in cells with low CDX2 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
4
20
0
Order By: Relevance
“…Given that constitutively active b-catenin does not directly regulate the Cdx2 promoter (Domon-Dell and Freund, 2002) and that Sox9, a target of b-catenin/ TCF4 that inhibits Cdx2 (Blache et al, 2004), is not upregulated during in vitro wound healing, the decline of Cdx2 in migrating cells may not depend on b-catenin. We reported previously that Cdx2 expression depends on the microenvironment and is downregulated by collagen type I via integrin-b1 and FAK (Brabletz et al, 2004;Benahmed et al, 2007). Interestingly, we show here that Integrin-b1 is upregulated during wound healing.…”
Section: Cdx2 Antagonizes Colon Cancer Cells Disseminationsupporting
confidence: 64%
“…Given that constitutively active b-catenin does not directly regulate the Cdx2 promoter (Domon-Dell and Freund, 2002) and that Sox9, a target of b-catenin/ TCF4 that inhibits Cdx2 (Blache et al, 2004), is not upregulated during in vitro wound healing, the decline of Cdx2 in migrating cells may not depend on b-catenin. We reported previously that Cdx2 expression depends on the microenvironment and is downregulated by collagen type I via integrin-b1 and FAK (Brabletz et al, 2004;Benahmed et al, 2007). Interestingly, we show here that Integrin-b1 is upregulated during wound healing.…”
Section: Cdx2 Antagonizes Colon Cancer Cells Disseminationsupporting
confidence: 64%
“…In fact, little is known about the regulation of CDX2 activity. Definitive studies have shown that phosphorylation of CDX2, by p38 MAP kinase, will regulate its transcriptional activity and modulate its interactions with other cofactors (8,11,12,33,35,64). The targeted degradation of CDX2 following its phosphorylation by Cdk2 has demonstrated that CDX2 homeostasis may be regulated by cell cycle machinery (12).…”
Section: Discussionmentioning
confidence: 99%
“…A study engrafting human colon cancers, freshly surgically resected, into the subcutis and the cecal wall of nude-mice, showed differential expression pattern with regard to the site of implantation [74]. Thus, the tumors showed a heterogeneous expression pattern at the time of surgical resection, but when subcutaneous injected into the mice, an increased homogeneous expression was observed.…”
Section: Cdx2 and The Tumor Environmentmentioning
confidence: 96%